A facile solution-based metallisation method without harsh conditions and expensive activators for paper substrate and its application in flexible supercapacitor. (July 2021) - Zhang, Qia; Kang, Ling; Zou, JianXiong; Huang, Chun; Gong, Zhiwei; Zhang, Jian
Graphical abstract: Highlights: The solution-based Au/Ni-P metallisation of cellulose papers was realized. Au/Ni-P composites offer high conductivity and mechanical stability. Au/Ni-P metallisation of cellulose papers exhibit excellent flexibility. Abstract: Sustainable and low-cost cellulose-based metallisation is the prerequisite for wearable and disposable electronics fabrication. In this paper, to realize the simplified, low-cost and high efficient metallisation, a new method had been proposed without both the noble metal activators and the corrosive chemicals. The modified electroless plating processes had been employed in activation and deposition procedure. The nickel ions were first physiadsorbed on the cellulose paper (CP) fibers and then reduced into clusters by reducing agent which can act as the seeds to initiate the electroless plating process. The gold galvanic displacement was conducted further to modify the nickel surface. Via these processes, the cellulose paper was metallised with Ni-P and Au/Ni-P successfully. The morphological and microstructural properties of the resulted Ni-P/CP and Au/Ni-P/CP hybrids were evaluated. The Ni-P/CP composites had a low surface resistance below 0.5 Ω sq -1 while the Au/Ni-P/CP composites are below 0.1 Ω sq -1 . The relationship between the mechanical and electrical properties with the plating parameters is discussed. The results indicated that Au/Ni-P/CP had good electrical conductivity and mechanical flexibility. Finally, the application demonstration for supercapacitor with the modified metallisation method was exhibited. This work offers a facile and non-toxic path to develop high-performance metallisation for functional cellulose-based materials.